2007
DOI: 10.1111/j.1745-7262.2007.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

The reversibility of sperm quality after discontinuing nandrolone decanoate in adult male rats

Abstract: The 14-week injection of low and high doses of ND decreases sperm quality and quantity in rats. These parameters were improved after discontinuing ND, but not recovered completely even when they are left untreated for 14 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
(41 reference statements)
0
20
0
1
Order By: Relevance
“…The side effects of anabolic steroids on the physiology and function of the reproductive system have been proved [3]. The side effects of steroids on the histology of testis [4], prostate [5], ovary, and uterus [6][7], spermatogenesis [8], genitalia malformation, and ovarian cyclical activity [1,[9][10][11] have also been shown. Ovarian and uterine histology and follicular score have been investigated after the ND treatment [6,7]; however, quantitative aspects of the ovary and oocytes have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…The side effects of anabolic steroids on the physiology and function of the reproductive system have been proved [3]. The side effects of steroids on the histology of testis [4], prostate [5], ovary, and uterus [6][7], spermatogenesis [8], genitalia malformation, and ovarian cyclical activity [1,[9][10][11] have also been shown. Ovarian and uterine histology and follicular score have been investigated after the ND treatment [6,7]; however, quantitative aspects of the ovary and oocytes have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Our results agree with studies which found that low and high doses of nandrrolone decrease sperm quality and quantity in rats in the form of low sperm count, decrease motile sperm fraction and decreased sperm with normal morphology. 26 The present study shows that the percentage of sperm motility decrease in group C compared with others this may be due to the mitochondrial content decrease with many swollen and disrupted mitochondria in rat soleus muscle after six weeks of treatment. 27 The result of S. Shokri et al 15 who studied the effect of exercise and supraphysiological doses of Nandrolone on sperm characteristics in male mature rats revealed that exercise and Nadrolone alone or in combination produced a significant decrease in sperm count and motility compared with the control group produced a significant decrease in sperm count and motility compared with the control group (sedentary rat without any injection or exercise).…”
Section: Discussionmentioning
confidence: 43%
“…The semen was obtained and analysed according to the procedure described by Seed et al [16,17]. The sperm was collected by cutting the distal region of the vas deferens of the rat in the present study.…”
Section: Sperm Collectionmentioning
confidence: 99%
“…In each rat, 300-400 spermatozoa were counted and the data were expressed as the total number of sperm/ml [16,17].…”
Section: Sperm Countmentioning
confidence: 99%
See 1 more Smart Citation